Demographic Change and Bank Profitability.Empirical Evidence from German Savings Banks - Marcel Thum; Michael Berlemann; Marco Oestmann (Verein für Socialpolitik, 2010)
Most European economies will experience significant demographic changes in the decades ahead. Due to low birth rates, populations are shrinking and ageing at the same time. This paper explores the impact of demographic change on the banking industry. A unique data set, which contains detailed information on almost 2.5 million accounts in 11 German savings banks, allows us estimating the socio-demographic determinants of retail profitability. Using a simulation model, we are able to predict the development of bank profitability due to demographic shifts up to 2025. One of the main findings is that the effects of population ageing will partially offset the impact of shrinking customer bases. While the decline in the size of the population reduces the customer base, ageing per se increases profitability as older customers typically generate higher profits for their banks.
Keywords: G21; J10; L10; 330; demography; banking; savings banks; profitability